Knowledge, Attitude and Participation of Fadama Users Group towards Fadama III Project Activities in Ebonyi State, Nigeria - Williams, Egwu Emeka (Asian Journal of Agriculture and Rural Development, 2015)
The study assessed the knowledge, attitude and participation of Fadama users group members towards Fadama III Project activities in Ebonyi State. Multiple and purposive sampling techniques were used to select 180 (one hundred and eighty respondents). Primary Data collected directly through Fadama III project facitlitators with questionnaire and interview schedule were used. Collected data analysed with both descriptive and inferential statistics. Result showed that Fadama III were groups towards Fadama project activities through formation of viable FUGs and apext FCAs (X = 3.1) formation group owned production assets such as cereal milk, rice milk, cassava processing plants, mini – tractors (x = 2.7), and managing of financial resources (x = 2.8). A coefficient of multiple determination show that above 64.2 percent change in the dependent variable was caused by changes in independent variables included in the regression model. Based on the findings, qualitative extension services should be provided for the farmers, massive enlightenment seminars, capital and involvement of farmers in the project planning and implementation will strengthen their participation in the programme.